Applications of capillary electromigration methods for separation and analysis of proteins (2017-mid 2021) - A review - Štěpánová, Sille; Kašička, Václav (Analytica chimica acta, 2022)
This paper provides a detailed overview of relevant developments in separation and analysis of proteins by capillary electromigration (CE) methods in the period 2017-mid 2021. The presented topics embrace sample preparation, suppression of protein sorption, control of electroosmotic flow, separations of proteins by the particular CE methods and protein identification and quantification by various detection techniques. To illustrate the wide usability of CE methods for protein analysis, the paper shows several novel applications of CE methods, such as quality control and characterization of protein biopharmaceuticals, determination of proteins in complex biomatrices, investigation of posttranslational modification, peptide mapping, interactions of proteins with other (bio)molecules and determination of their physicochemical and biochemical characteristics.
Keywords: Capillary electrochromatography; Capillary electrophoresis; Peptides; peptidy; Isoelectric focusing; elektroosmóza; peptidové mapování; elektroforéza kapilární; Electrophoresis, Capillary; Peptide Mapping; Review; Proteins; Affinity electrophoresis; Electroosmosis; proteiny